The Effect of Spent Coffee Grounds to the Growth of Solanum lycopersicum (Tomato) - Baranda, Romar A. (Animo Repository, 2021)
Six billion tonnes of spent coffee grounds (SCG) are thrown untreated into landfills, leading the spent coffee grounds to leach organic pollutants that may potentially harm bodies of water and emit methane, a greenhouse gas, into the atmosphere. Studies have confirmed that the ratio of carbon and nitrogen (C: N) of SCG is ideal for plant fertilizers. This study focused on determining the effects of SCG on the growth of tomato plants using four parameters: the number of leaves, the average leaf surface area, and the relative growth rate. The study used an experimental research design to study the causal relationship between SCG treatments and plant growth. Tomato seeds were grouped into four and sown on separate pots. The study used three trials, each containing different weights of SCG, namely: 0 g, 5 g, 9 g, and 14 g. The SCG treatments were applied after germination using the side-dressing method. The number of expanded leaves, leaf surface area, and relative growth rate of the tomato plants were observed every five days for 45 days. The researchers found that SCG treatments that exceeded SCG-5 displayed adverse effects on the growth of the tomato. Thus, the relative growth rate and SCG treatments of over 5 g are inversely related to one another. Results show that SCG-5 had the highest positive effect on plant growth in terms of all the parameters. The researchers can then conclude that SCG-5 is an effective alternative fertilizer that improves plant growth.